In Situ Observation of Two-Dimensional Electron Gas Creation at the Interface of an Atomic Layer-Deposited Al2O3/TiO2Thin-Film Heterostructure - Seok, Tae Jun; Liu, Yuhang; Choi, Ji Hyeon; Kim, Hye Ju; Kim, Dae Hyun; Kim, Sung Min; Jang, Jae Hyuck; Cho, Deok Yong; Lee, Sang Woon; Park, Tae Joo (Chemistry of Materials, 2020)
A two-dimensional electron gas (2DEG) was formed at the interface of an ultrathin Al2O3/TiO2 heterostructure that was fabricated using atomic layer deposition (ALD) at a low temperature (<300 °C) on a thermally oxidized SiO2/Si substrate. A high electron density (∼1014 cm-2) and mobility (∼4 cm2 V-1 s-1) were achieved, which are comparable to those of the epitaxial LaAlO3/SrTiO3 heterostructure. An in situ resistance measurement directly demonstrated that the resistance of the heterostructure interface dropped significantly with the injection of trimethylaluminum (TMA), indicating that oxygen vacancies were formed on the TiO2 surface during the TMA pulse in the ALD of Al2O3 films, such that they provide electron donor states to generate free electrons at the interface of the ultrathin Al2O3/TiO2 heterostructure. The activation energy of the electron donor states to move to the Ti 3d conduction band plays an essential role in the electrical characteristics of the 2DEG. Interestingly, the donor state level can be tailored by the control of TiO2 crystallinity, which eventually adjusts the electron density. The activation energy was decreased to less than 20 meV to generate ultrashallow donor states while improving the TiO2 crystallinity, such that the 2D electrons become readily delocalized, even at room temperature, to create a 2DEG.
Keywords: Atomic layer deposited; Electrical characteristic; Heterostructure interfaces; High-electron-density; In-situ observations; Situ resistance measurements; Thermally oxidized; Two-dimensional electron gas (2DEG)